People’s perceptions towards herbal medicines: a quantitative study of motivating factors - Ansari, Azhar Mustafa; Khan, M. Razaullah; Sikandar, M. A. (International Journal of Scientific Reports, 2025)
Background: Herbal medicines, derived from natural ingredients without chemical synthesis, form the foundation of various traditional healthcare systems in India. With the growing incidence of chronic diseases, antibiotic resistance, and side effects of synthetic drugs, there is an increased global shift towards natural and holistic treatment options. This has renewed interest in herbal medicine, especially in countries with a strong tradition in its use, like India. Methods: The present study adopted a quantitative research approach to examine consumer perceptions and purchasing behavior toward herbal medicines. A structured questionnaire was used to collect data from 250 respondents in Hyderabad, India. Statistical techniques such as descriptive statistics, factor analysis, correlation, and multiple regression were employed to analyze the data. Results: The findings revealed that factors such as health and safety, effectiveness and reliability, trust and brand perception, and environmental and ethical considerations significantly influence consumers’ purchase intentions and their likelihood to recommend herbal medicines. In contrast, economic and availability and cultural and social factors did not show any significant influence on purchase behavior. Conclusions: The study concludes that the growing preference for herbal medicines is largely driven by perceived health benefits, trust in product quality, and ethical concerns. These insights may help marketers and policymakers design more effective awareness and distribution strategies to promote the adoption of herbal products.